(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2018)
Background: Electricity and water are most important utilities in the hotel. They also contribute to majority of the utility costs/expenses. Controlling the usage of electricity and water and other utilities with help of technology and training will improve the profit margins of the hotel. Objective: To study the impact of utility cost on bottom line of the hotels and to find ways to save or control the utility expenses. Methodology: The study was conducted by taking 7 hotels and 10 employees as the sample size (n=10). The survey questionnaires were filled administered with face to face interviews with the respondents. Results: The findings of this research revealed that utility expenses contribute to about 4-10% of the total expenses. About 40 % hotels have environmental friendly installations and 57% of respondents agreed these installations are helpful. Conclusion: Controlling the utility expenses not only improves the profit margins, however, it also makes a hotel more environmental friendly.